Fish complement C4 gene evolution and gene/protein regulatory network analyses and simulated stereo conformation of C4–MASP–2 protein complex. Issue 107 (December 2020) - Li, Lisen; Shen, Yubang; Xu, Xiaoyan; Yang, Weining; Li, Jiale
Abstract: Complement C4 is a central protein by acting as pivotal molecule in the activation of the complement system. More than a decade ago, C4 gene duplication had been found in several species including fish, revealing the evolutionary origin of C4 gene. However, the evolutionary pattern and systematic function of C4 are still limited. In this study, C4 D and H types in different species groups were completely diverged. The codon usage of C4 H type in higher vertebrates were much closer to their own genome environment, in contrast to lower vertebrates, suggesting that the evolution may provide the dynamic for homogeneous codon usage between specific gene and genome. Multiple C4 sequence alignment showed that the sequences were conserved among different species. However, sequence similarity was obviously different between species C4 D and H type. Negative selection pressure was found on C4 gene evolution and it may be one of the possible reasons for the sequence broad similarity and conservation among interspecies. Proteins from C4 protein–protein interaction (PPI) network were enriched in more hematopoiesis, infections, diseases and immune–related pathways in human than zebrafish. The result suggested that the functional complexities of C4 isotypes are distinct in species from different evolutionary positions. The simulated C4 protein structures between human and grass carp shared structural similarity and the stereo structures of grass carp C4–MASP–2 protein complexes were further simulated according to a study of human. These results suggested that the interaction between C4 and MASP–2 proteins may also exist in grass carp. Our results can provide an insight for the evolutionary process of C4 and better understanding to the potential mechanism of interaction between C4 and MASP–2 in fish species. Highlights: Codon usage of C4 gene is much closer to genomic environment in higher vertebrates. C4 genes from each species groups underwent negative selection pressures. Functional complexities of two C4 isotypes tend to distinct in species from different evolutionary positions. Protein structural analysis showed that C4 may have theoretical interaction with MASP–2 protein in grass carp.